Detection of Malaria Parasites in donated blood in Zimbabwe using the rapid SD Bioline test kit. - Samakande, Danai; Mandisodza, Arthur; Chikwasha, Vasco; Mavenyengwa, Rooyen; Mavunganidze, George; Parirewa, Judith (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The potential of transfusion transmitted malaria infection in Zimbabwe is high because blood donors are not screened for malaria infection. The study was carried out to assess possible malaria infection in blood donors from malaria endemic regions using the rapid and routine microscopy methods. Experts repeated the microscopy method on samples that were positive with the rapid SD Bioline immunochromatography method. All blood donors were negative for malaria using the conventional thin and thick blood film methods. Eight (4.5%) blood donors were positive using the SD Bioline immunochromatography method. Repeats of the microscopy tests on eight positive SD Bioline results by experts were negative. Bulawayo, Zimbabwe’s second largest city, had the highest malaria positive donor blood. There was an association between malaria infection and Rh D positive blood donors. It can be concluded that screening blood donors for malaria using more sensitive techniques is necessary to avoid transfusion-transmitted malaria infection.